Herramientas de autor y su aporte a la práctica pedagógica en el proceso de enseñanza y aprendizaje del inglés (2018)
This research analyzes the contribution of author tools to the pedagogical practice of teachers in the areas of English. For this, a diagnostic test was applied that allowed to identify the state of the pedagogical practice of the teachers of the Departmental Educational Institution Natania in the area of English. Subsequently, a training process was developed with the inclusion of the author tool CUADERNIA in the areas of English, during an academic period. Finally, pedagogical strategies were formulated with the use of the tool applied to the English students of the institution. The study showed that students and teachers were motivated with the use of technology, considering it an effective tool to reinforce knowledge in the areas of English. It was concluded that the application of the author tool as a didactic mediation strategy contributes to the strengthening of the pedagogical practice of the teachers and, at the same time, to the learning of the students